2007
DOI: 10.1111/j.1365-2648.2007.04312.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing cultural sensitivity: nursing students’ experiences of a study abroad programme

Abstract: The findings suggest that study abroad is a useful strategy for bridging the theory-practice divide. However, further research is needed with larger and more diverse students to test the generalizability of the findings. Longitudinal research is also needed to assess the impact of study abroad programmes on the deliver of culturally sensitive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 13 publications
5
108
0
3
Order By: Relevance
“…An international study program of Danish nursing students was developed to give students a global experience by Ruddock and Turner (2007). This qualitative study concluded that cultural sensitivity could be developed in study abroad programs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…An international study program of Danish nursing students was developed to give students a global experience by Ruddock and Turner (2007). This qualitative study concluded that cultural sensitivity could be developed in study abroad programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Qualitative research of study abroad programs has shown an approach that can prepare students for the workforce and diverse patient populations (Green, et al, 2008;Ruddock & Turner (2007). Results of programs such as this immersion course can inform not only future programs but emphasize holistic nursing in course curricula.…”
Section: Limitationsmentioning
confidence: 99%
“…However, in some cases communication difficulties can impair the development of intercultural competencies. Occasionally, these difficulties can lead to situations where students and scholars start to totally withdraw from interactions and ultimately become isolated (Koskinen & Tossavainen, 2003;Ruddock & Turner de, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This has made it difficult to decipher the specific benefits that study tours can provide. Generally, however, studies tend to posit that students who participate in study tours enhance their knowledge of global geography, the customs and history of these places, and their ability to navigate in unfamiliar cultural settings [8], [9].…”
Section: B Educational Potentials and Challenges Of Overseas Study Tmentioning
confidence: 99%